Caos en la ciudad - Pérez Him, Enrique, 1982-; Escalante, Ariel, 1984- (Producciones Jems : Sistema Estatal de Radio y Televisión, 2012)
How does the progress of a city influence the lives of its inhabitants? This question is the one that tries to answer Chaos in the city, the project selected by Panama for Doctv Latin America. Listening to the voices of Panamanian citizens, director Enrique Pérez Him, along with producer Isabella Gálvez Peñafiel and a team of Panamanian and foreign filmmakers, show the accelerated development of one of the fastest growing economies in all of Latin America. This growth is mainly reflected in the different construction megaprojects that in recent years have been adorning the capital of this small country and many in Panama City boast of the current development, but to what extent can we talk about developing? --